Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1161/01.hyp.0000144271.59333.a7
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Sympathoinhibitory Effects of Cardiac Resynchronization Therapy in Severe Heart Failure

Abstract: Abstract-Evidence is available that in heart failure, cardiac resynchronization therapy by biventricular pacing improves myocardial function and exercise capacity. Whether this is accompanied by a sustained inhibition of heart failure-dependent sympathoexcitation is uncertain. In 11 heart failure patients (meanϮSEM age, 68.4Ϯ1.5 years) in New York Heart Association (NYHA) class III and IV under medical treatment with an intraventricular conduction delay (QRS duration Ն130 ms), with a markedly depressed left ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 40 publications
(31 reference statements)
3
33
0
Order By: Relevance
“…These data for sensitivity are similar to those reported by others [25]. During each experimental session, BP was monitored by a finger photopletismographic device (Finapres 2300, Ohmeda) capable of providing accurate beat-to-beat systolic and diastolic values [6][7][8][12][13][14][15]17,18]. Heart rate was monitored beat-to-beat by a cardiotachometer triggered by the R wave of an EKG lead.…”
Section: Measurementssupporting
confidence: 84%
See 3 more Smart Citations
“…These data for sensitivity are similar to those reported by others [25]. During each experimental session, BP was monitored by a finger photopletismographic device (Finapres 2300, Ohmeda) capable of providing accurate beat-to-beat systolic and diastolic values [6][7][8][12][13][14][15]17,18]. Heart rate was monitored beat-to-beat by a cardiotachometer triggered by the R wave of an EKG lead.…”
Section: Measurementssupporting
confidence: 84%
“…Multiunit recording of MSNA was obtained from a microelectrode inserted in a peroneal nerve posterior to the fibular head, as reported previously [6][7][8]12,13,17,18]. Integrated nerve activity was monitored by a loud-speaker, displayed on a storage oscilloscope (model 511A, Tektronix), and continuously recorded with BP and heart rate on an ink polygraph.…”
Section: Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cha et al [25] found that clinical and cardiac functional improvements were paralleled by significant improvements in NE reuptake function as measured by metaiodobenzylguanidine ( 123 I-MIBG), an NE analog, uptake and retention after CRT for advanced cardiomyopathy. Also, CRT inhibits arterial baroreflex mediated sympathoexcitation occurring in CHF, and, therefore, reduces adrenergic nerve outflow measured by microneurography [26,27].…”
Section: Discussionmentioning
confidence: 99%